Avaliação de herbicidas para dessecação da Soja como alternativa em substituição ao Paraquat - Rosa, Lucas Formentini (Universidade Federal do Tocantins, 2021)
Soy is one of the most important crops in the Brazilian agribusiness, with a production of 124.845 million tons with an average yield of 3,379 kg ha-1. Harvesting is an important step in the soy production process, the use of applied desiccant herbicides facilitates the operation. Paraquat is a highly toxic product, which can cause the death of humans and animals, so the objective was to evaluate possible active ingredients that have efficacy similar to the herbicide paraquat, in order to promote the desiccation of soy. The experiment was carried out in the experimental area of the Research Support Foundation of the North Export Corridor, located in the city of Balsas-MA, the design used was a randomized block with 12 treatments and 4 repetitions. The treatments used consisted of three herbicides with different active ingredients. 7 evaluations were performed at (1, 3, 5, 7, 10, 12 and 14 DAA) to evaluate the defoliation percentage. Among the treatments studied, those indicated for the replacement of paraquat are treatments T2 (Diquat + Hydrocarbon dosage: 2 + 0.5 l / ha), T3 (Diquat + Hydrocarbon dosage: 1 + 0.5 l / ha), T6 (Diquat + Flumioxazin + Hydrocarbon dosage: 1 + 0.05 + 0.5 l / ha) and T7 (Diquat + Flumioxazin + Hydrocarbon dosage: 1 + 0.1 + 0.5 l / ha), which have diquat as an active ingredient.